Utilization of Solar Panel Energy for Electricity in Seuseupan Village, Sukabumi - Teguh Puja Negara; Syarif Hidayatulah; Agus Ismangil (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2026)
Limited public lighting in rural areas remains a significant obstacle affecting community safety, mobility, and socio-economic activities. This Community Service Program aims to improve energy independence in Seuseupan Village, Caringin District, Sukabumi Regency, through the implementation of a solar panel-based public lighting system. Implementation methods included field observations, Focus Group Discussions (FGDs), technical training on solar energy, installation of solar lamps in strategic locations, and monitoring and evaluation of system performance and program impact. Results showed that the solar panel installation improved the quality of lighting in public areas, strengthened people's sense of security at night, and reduced electricity costs by 37%. Furthermore, increased access to lighting contributed to a 23% increase in community economic activity while also increasing community knowledge and participation in the management of renewable energy technologies. This program demonstrates that utilizing solar energy is an effective, economical, and sustainable solution to support village infrastructure development. The program's implementation is based on the goal of achieving energy-independent villages and smart villages, and has the potential to be replicated in other regions with similar geographic conditions and needs. The program's success is measured not only by the technical aspects of installing the solar panel system, but also by the development of community awareness of the importance of utilizing clean energy as an alternative energy source. A participatory approach involving village governments, community groups, and implementers fosters a sense of ownership of the constructed facilities, thereby supporting the continuity of the operational and maintenance systems. Therefore, this community service model can serve as a reference for renewable energy-based community empowerment programs that support the achievement of sustainable development goals (SDGs), particularly in the areas of clean energy, infrastructure development, and improving the quality of life of rural communities.